Effects of yoga training on body composition, cardiovascular and biochemical parameters in healthy adult male volunteers - Indranil Manna (Al Ameen Medical College, 2017)
Introduction: Physical inactivity and stressful condition reduces the fitness level which may lead to cardiovascular diseases (CVD). Objectives: To study the effects of yoga on body composition, cardiovascular parameters and lipid profile on healthy adult males. Methods: A total of 60 healthy male volunteers within the age group of 18-24 years were included and were divided into two groups: (a) Control Group (N=30) and Experimental Group (N=30). Yoga training was given for 60 min per day, 06 days per week for 12 weeks in the experimental group. In the control group no yoga training was given. Assessment of body composition, cardio-respiratory fitness and lipid profile were performed in both the groups before yoga training (0 week) and after the training (12 weeks). Results: Significant reduction (P<0.05) in percentage of body fat, systolic blood pressure, resting heart rate, total cholesterol (TC), triglyceride (TG) and low density lipoprotein cholesterol (LDL-C) levels were noted among the experimental group after 12 weeks of yoga training when compared to baseline data (0 week). On the other hand, significant increase (P<0.05) in high density lipoprotein cholesterol (HDL-C) was noted in the experimental group after 12 weeks of yoga training when compared to baseline data (0 week). Conclusions: These changes might be due to yoga training. Regular yoga practice improves body composition and cardiovascular status and maintains lipid profile.